Hubungan Ekologi Dengan Pelestarian Lingkungan - putra, Aditya Pratama; April Liansyah; Ajansyah (CV. ITTC INDONESIA, 2023)
Ecosystem is an ecological system formed by an inseparable interrelationship between living things and their environment. Ecosystem can also be said as a whole and comprehensive order of unity among all elements of the environment that influence each other. Ecology is the science of the interrelationships between living things with each other and with non-living things around them. This writing is intended to find out clear information about the ecological relationship with the environment and proper conservation of the environment. The discourse on environmental conservation has become an actual issue amid the threat of the global environmental crisis. Because the environmental crisis is considered to be the biggest problem of this century which has an impact on the inhabitants of the present world and future generations. Experts have mapped that the environmental crisis has caused various disasters, climate change, global warming, reduced quality of life and the threat of future destruction of the earth. Therefore, people throughout the world continue to look for joint solutions to overcome this crisis. Formulating environmental conservation from the point of view of the current situation is important. Therefore based on the science of environmental conservation ecology is very influential on each other.